Improving Food Systems: A Participatory Consultation Exercise to Determine Priority Research and Action Areas in Viet Nam - Nguyen, Trang; van den Berg, Marrit; Raneri, Jessica E.; Huynh, Tuyen (Frontiers in Sustainable Food Systems, 2021)
With increased burden of malnutrition on global health, there is a need to set clear and transparent priorities for action in food systems at a global and local level. While priority settings methods are available for several adjacent domains, such as nutrition and health policies, setting priorities for food system research has not been documented and streamlined. The challenges involve food systems’ multisector, multi-stakeholder and multi-outcome nature. Where data exists, it is not easy to aggregate data from across food system dimensions and stakeholders to make an informed analysis of the overall picture of the food system, as well as current and potential food system trade-offs to inform research and policy. Once research priorities are set, they risk staying on paper and never make their ways to concrete outputs and outcomes. In this paper, we documented and assessed the inclusive process of setting research priorities for a local food system, taking Vietnamese food systems as a case study. From this exercise, we examined how priority setting for food systems research could learn from and improve upon earlier priority setting research practices in other domains. We discussed the lessons for research and policies in local food systems, such as the need for a concrete follow-up plan accompanying the priority setting process.